2012
DOI: 10.1074/jbc.m111.277178
|View full text |Cite
|
Sign up to set email alerts
|

Functional Selective Oxytocin-derived Agonists Discriminate between Individual G Protein Family Subtypes

Abstract: Background:The oxytocin receptor couples to multiple G proteins, leading to different physiological responses. Results: We screened for functional selective oxytocin receptor agonists and identified two analogs that activate individual G i subunits. Conclusion: Functional selective analogs discriminate among different receptor conformations coupled to G i proteins. Significance: These compounds will contribute to the development of selective drugs with new selectivity and therapeutic profiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
154
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 163 publications
(163 citation statements)
references
References 49 publications
5
154
0
4
Order By: Relevance
“…In human amnion, OTR was found to initiate its pro-inflammatory signal transduction via G αi -dependent signalling [53], whilst mainly G αq/11 coupling has been found to be involved in OT-induced myometrial contractions [52]. Recent findings show ligand-dependent discrimination of G protein family subtypes [54]. It has been suggested that binding of OTRantagonist, Atosiban, to myometrial OTR drive anti-labour signalling in the myometrium through inhibition of G αq/11 -dependent OT-mediated contractions but initiate pro-labour signalling in the amnion via G αi , resulting in activation of inflammation [53] (Figure 2).…”
Section: Inflammationmentioning
confidence: 99%
“…In human amnion, OTR was found to initiate its pro-inflammatory signal transduction via G αi -dependent signalling [53], whilst mainly G αq/11 coupling has been found to be involved in OT-induced myometrial contractions [52]. Recent findings show ligand-dependent discrimination of G protein family subtypes [54]. It has been suggested that binding of OTRantagonist, Atosiban, to myometrial OTR drive anti-labour signalling in the myometrium through inhibition of G αq/11 -dependent OT-mediated contractions but initiate pro-labour signalling in the amnion via G αi , resulting in activation of inflammation [53] (Figure 2).…”
Section: Inflammationmentioning
confidence: 99%
“…Even as OT has been recently reported to improve cognitive deficits in autistic patients (Modi and Young, 2012), its use is hampered by several of the following factors: 1) OT does not cross the blood-brain barrier and is administered intranasally, with unknown pharmacokinetics; 2) it also binds to and activates the V1aR and V1bR, which are highly expressed in the brain, where they exert different and even opposite effects (Pittman and Spencer, 2005); and 3) OT promotes the coupling of the OTR to different G proteins and b-arrestins (Busnelli et al, 2012) and, consequently, activates multiple signaling pathways whose precise roles within the brain are currently unknown. The development of more selective, potent, and therefore, longer-lasting analogs acting on brain is a priority in the field to understand how (in terms of biologic mechanisms) and where (in terms of neural specificity) OT exerts its effects.…”
Section: Introductionmentioning
confidence: 99%
“…All G protein subunits coding plasmids for BRET experiments (Galphaq-97-Rluc, Galphai1-91-Rluc, Galphai2-91-Rluc, Galphai3-91-Rluc, GalphaoA-91-Rluc8 or GalphaoB-91-Rluc8) were previously described (Busnelli et al, 2012;Saulière et al, 2012). Ga oA C351I (Ga oA(PTX-r) ) and Ga oB C351I (Ga oB(PTX-r) ) plasmids were purchased from Missouri S&T cDNA Resource Center.…”
Section: Constructsmentioning
confidence: 99%
“…To investigate the specific ligand-induced G protein activation by wild-type SST5, we co-transfected HEK293 with wild-type SST5, Ga-RLuc, Gc2-GFP10 and complementary Gb1 subunit. In particular, we tested six different Ga-RLuc subunits (Ga i1,i2,i3,q,oA,oB ) by transfecting the corresponding plasmids (described in Saulière et al, 2012;Busnelli et al, 2012). A significant (P,0.001 versus PBS treated cells) BRET signal ratio decrease was obtained following wild-type SST5 activation by specific agonist BIM23206 (100 nM) with the Ga i1,2,3 and Ga oA,B subunits, whereas no decrease was observed with Ga q , as shown in Fig.…”
Section: G Proteins Activated By Wild-type Sst5mentioning
confidence: 99%
See 1 more Smart Citation